PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI DI DINAS PEMUDA DAN OLAHRAGA PROVINSI SUMATERA BARAT - Ichsan Khalis; Elfiswandi; Zefriyenni (Journal Publicuho, 2025)
This study aims to examine the effect of work environment, organisational culture, and work discipline on performance mediated by organisational commitment. A quantitative approach with hypothesis testing techniques was used in this study. There were 77 samples with the saturated sample technique, namely, all employees at the Youth and Sports Office of West Sumatra Province. Data were collected through distributing questionnaires online and processed using SmartPLS 3.0 software with structural equation modelling techniques. The results showed that work environment, organisational culture, and work discipline each had a positive and significant effect on organisational commitment. Work discipline and organisational commitment each have a positive and significant effect on performance, but an insignificant effect was found by the work environment and organisational culture. The effect of organisational culture and work discipline on performance through the mediation of organisational commitment was found to be positive and significant, but insignificant mediation by organisational commitment on the relationship between work environment and performance was found. The implications of the research emphasise the importance of maintaining the commitment and loyalty of employees in government agencies in order to provide the best empowerment to the community.